Application of spatial transcriptome technologies to neurological diseases - Ya, Dongshan; Zhang, Yingmei; Cui, Qi; Jiang, Yanlin; Yang, Jiaxin; Tian, Ning; Xiang, Wenjing; Lin, Xiaohui; Li, Qinghua; Liao, Rujia (Frontiers in Cell and Developmental Biology, 2023)
Spatial transcriptome technology acquires gene expression profiles while retaining spatial location information, it displays the gene expression properties of cells in situ. Through the investigation of cell heterogeneity, microenvironment, function, and cellular interactions, spatial transcriptome technology can deeply explore the pathogenic mechanisms of cell-type-specific responses and spatial localization in neurological diseases. The present article overviews spatial transcriptome technologies based on microdissection, in situ hybridization, in situ sequencing, in situ capture, and live cell labeling. Each technology is described along with its methods, detection throughput, spatial resolution, benefits, and drawbacks. Furthermore, their applications in neurodegenerative disease, neuropsychiatric illness, stroke and epilepsy are outlined. This information can be used to understand disease mechanisms, pick therapeutic targets, and establish biomarkers.